Feasibility and acceptability of a cancer symptom awareness intervention for adults living in socioeconomically deprived communities - Pamela Smith; Stephanie Smits; Sioned Owen; Fiona Wood; Grace McCutchan; Ben Carter; Adrian Edwards; Michael Robling; Julia Townson; Kate Brain (BMC, 2018)
Abstract Background Cancer survival rates in the UK are lower in comparison with similar countries in Europe and this may be linked to socioeconomic inequalities in stage of cancer diagnosis and survival. Targeted cancer awareness interventions have the potential to improve earlier symptomatic diagnosis and reduce socioeconomic inequalities in cancer outcomes. The health check is an innovative, theory-based intervention designed to increase awareness of cancer symptoms and risk factors, and encourage timely help seeking among adults living in deprived communities. Methods A prospective, non-randomised evaluation was undertaken to test the feasibility and acceptability of the health check for adults aged 40 years and over living in deprived areas of Wales. Primary outcomes included recruitment and retention of approximately 100 adults, reach to participants in the lowest deprivation quartile, and intervention acceptability. Secondary outcomes included self-reported cancer symptom recognition, help-seeking behaviours and state anxiety pre/post intervention. Results Of 185 individuals approached, 98 (53%) completed the intervention. Sixty-six of 98 participants were recruited from community settings (67%) and 32 from healthcare settings (33%), with 56 (57%) from the lowest deprivation quartile. Eighty-three (85%) participants completed follow-up assessment. Participants recognised on average one extra cancer symptom post intervention, with improved recognition of and anticipated presentation for non-specific symptoms. State anxiety scores remained stable. Qualitative interviews (n = 25) demonstrated that the intervention was well received and motivated change. Conclusions Recruitment was feasible in community and healthcare settings, with good reach to adults from low socioeconomic groups. The health check intervention was acceptable and demonstrated potential for improved cancer awareness and symptom presentation, especially for non-specific symptoms, in communities most affected by cancer.